One-Year Impact of Occupational Exposure to Polycyclic Aromatic Hydrocarbons on Sperm Quality - Mª Victoria Peña-García; Mª José Moyano-Gallego; Sara Gómez-Melero; Rafael Molero-Payán; Fernando Rodríguez-Cantalejo; Javier Caballero-Villarraso (Antioxidants, 2024)
Background: Polycyclic aromatic hydrocarbons (PAHs) have toxic potential, especially as carcinogens, neurotoxins, and endocrine disruptors. The objective of this study is to know the impact of exposure to PAHs on the reproductive health of male workers who operate in solar thermal plants. Methods: Case–control study. A total of 61 men were included: 32 workers exposed to PAH at a solar thermal plant and 29 unexposed people. Seminal quality was studied both at the cellular level (quantity and quality of sperm) and at the biochemical level (magnitudes of oxidative stress in seminal plasma). Results: In exposure to PAHs, a significantly higher seminal leukocyte infiltration was observed, as well as lower activity in seminal plasma of superoxide dismutase (SOD) and a reduced glutathione/oxidised glutathione (GSH/GSSG) ratio. The oxidative stress parameters of seminal plasma did not show a relationship with sperm cellularity, neither in those exposed nor in those not exposed to PAH. Conclusion: One year of exposure to PAH in a solar thermal plant does not have a negative impact on the sperm cellularity of the worker, either quantitatively (sperm count) or qualitatively (motility, vitality, morphology, or cellular DNA fragmentation). However, PAH exposure is associated with lower antioxidant capacity and higher leukocyte infiltration in seminal plasma.